Assessment of the Compliance of Cystitis Management According to French Recommendations through the Analysis of Prescriptions Collected in Community Pharmacies - Arthur Piraux; Ramy Hammoud; Jérémie Riou; Souhil Lebdai; Sébastien Faure (MDPI AG, 2022)
Urinary tract infections, especially cystitis, are common infections; they are the second most prevalent cause of antibiotic prescriptions in community pharmacies. To reduce antimicrobial resistance, guidelines are revised regularly. This study aims to assess compliance between prescriptions collected in community pharmacies and French cystitis guidelines. A treatment is considered compliant if the nature, dosage, and duration of the antibiotics are correct. Only women aged 18-65 years with a diagnosis of cystitis were eligible. The participation of 16 pharmacies resulted in 303 prescriptions. Most infections were classified as uncomplicated cystitis (79.2%), general practitioners were the prescribers in more than 9 out of 10 cases, and fosfomycin trometamol was the antibiotic dispensed for 1 in 2 women. An average compliance of 66% was observed, but with disparities according to the type of cystitis. Two-thirds of cases of uncomplicated cystitis and recurrent cystitis followed the recommendations, whereas only 15% of cystitis cases that were at risk of complication did so. The inclusion of a urine examination in uncomplicated cystitis decreased the overall compliance rate to 5.8%. These results show the essential role played by pharmacists; they are the last line of defence before dispensing antibiotics. They must know the recommendations in order to apply them.